Rectal prolapse in an emu (dromaius novaehollandiae): a case report (2011)
Rectal prolapsed is the protrusion of all layers of the rectum through the anal orifice as an elongated cylindrical mass (Aronson 2003). It usually occurs in patients secondary to tenesmus from urogenital or anorectal disease. It has been reported in small animals with no record of breed or sex predisposition, although an observation of a higher incidence in younger animals has been made (Burrows and Ellison, 1991). In small animals the condition is associated with gastrointestinal parasitism, typhlitis, colitis, proctitis, tumors, rectal foreign bodies, and urolithiasis (Burrows and Ellison, 1990; Aronson 2003). In birds, especially emus and ostriches, the condition has been associated with cryptosporidiosis (Bezuidenhout et al., 1993; Penrith and Burger, 1993; Penrith et al., 1994; Behzadi et al., 2009), Aspergillus flavus and Candida albicans induced enteritis (Saez et al., 1979, Huchzermeyer, 1999) and immunosuppression due to the quality of feed, water and hygiene (Behzadi et al., 2009). Cloacal prolapse has also been linked with impaction due to poor nutrition or eating habits of the ratites (Gulbahar et al., 2000). Impaction is one of the most common problems seen in ratites, especially in farmed ostrich (Gulbahar et al., 2000). Impactions may occur at any age, but are most common in 3 to 6 months juveniles (Gulbahar et al., 2000). Birds with partial impaction may present with a chronic history of lethargy, anorexia with evidence of weight loss, with pelletized feces, and at presentation are weak with persistent tenesmus leading to cloacal prolapse (Gulbahar et al., 2000). Ostrich and emu farming are still relatively new in Nigeria. Farmers keep ratio of two to twelve young or adult ostriches and emus in farms. This paper reports a case of rectal prolapse in a young emu which to the authors' knowledge is the first in this environment